THRAATCHATHI CHOORANAM, A POLYHERBAL SIDDHA FORMULATION PROTECTS AGAINST ISOPROTERENOL INDUCED BIOCHEMICAL ALTERATIONS IN RATS - RAMAKRISHNAN GANAPATHY,; GAYATHRI VEERARAGHAVAN,; GIRISH RAMESH,; GAYATHRI KARANAM,; SIVARAMAN GURUSAMY,; SARAVANA BABU CHIDAMBARAM, (International Journal of Pharma and Bio Sciences, 2016)
Current therapeutic approaches in the management of cardiovascular diseases like acute myocardial infarction, cardiac reperfusion injury and hypertension produce side effects on myocardium on long term treatment. The present study was undertaken to investigate the ardioprotective effects of Thraatchathi chooranam, a polyherbal siddha formulation against Isoproterenol (ISO) induced biochemical alterations in Sprague wley rats. Administration of ISO in rats significantly elevated plasma creatine kinase (CK-MB), lactate dehydrogenase (LDH), alanine transaminase (ALT), aspartate transaminase (AST) and lipids such as total cholesterol (TCHO), triglycerides (TG) and low density lipoproteins with a concurrent decrease in high density lipoproteins (HDL) levels in comparison to vehicle treated control rats. Pretreatment with Thraatchathi chooranam (50 & 100 mg/kg, p.o) for a period of 28 days significantly prevented these alterations in ISO challenged rats. Results were comparable with that of the standard anti-oxidant Vit E. These data’s provides evidence on the cardioprotective effects of Thraatchathi chooranam, at least, partly through the anti-oxidant chemical principles and mechanism.